Engaging with Uncertainty and Complexity: A Secondary Analysis of Primary Care Responses to Intimate Partner Violence - Claire Gear; Jane Koziol-McLain; Elizabeth Eppel (SAGE Publishing, 2021)
Complex problems generate uncertainty. The number and diversity of interactions between different health professionals, perspectives, and components of the problem makes predicting an outcome impossible. In effort to reduce the uncertainty of intimate partner violence interventions, health systems have developed standardized guidelines and protocols. This paper presents a secondary analysis of 17 New Zealand primary care professional narratives on intimate partner violence as a health issue. We conducted a complexity-informed content analysis of participant narratives to explore uncertainty in greater depth. This paper describes three ways primary care professionals interact with uncertainty: reducing uncertainty, realizing inherent uncertainty, and engaging with uncertainty. We found dynamic patterns of interaction between context and the experience of uncertainty shape possible response options. Primary care professionals that probed into uncertainty generated new understanding and opportunities to respond to intimate partner violence.